2012
DOI: 10.1016/j.cub.2012.09.014
|View full text |Cite|
|
Sign up to set email alerts
|

The Retinotopic Organization of Striate Cortex Is Well Predicted by Surface Topology

Abstract: Summary In 1918, Gordon Holmes combined observations of visual field scotomas across brain lesioned soldiers to produce a schematic map of the projection of the visual field upon the striate cortex [1]. One limit to the precision of his result, and the mapping of anatomy to retinotopy generally, is the substantial individual variation in the size [2,3], volumetric position [4], and cortical magnification [5] of area V1. When viewed within the context of the curvature of the cortical surface, however, the bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
268
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(285 citation statements)
references
References 28 publications
15
268
1
1
Order By: Relevance
“…Prior work has shown that the 10 V1-V3 maps have highly regular topography and are well aligned to measures of anatomy, such as 11 surface curvature (Hinds et al, 2008;Benson et al, 2012;2014) and myelination (Abdollahi et al, 2014), 12 and to measures of function such as resting-state connectivity (Raemaekers et al, 2014; Bock et al, 13 2015). Therefore, these maps are likely to be well aligned across subjects, and averaging will preserve 14 many of the retinotopic features found in the maps of individual subjects.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Prior work has shown that the 10 V1-V3 maps have highly regular topography and are well aligned to measures of anatomy, such as 11 surface curvature (Hinds et al, 2008;Benson et al, 2012;2014) and myelination (Abdollahi et al, 2014), 12 and to measures of function such as resting-state connectivity (Raemaekers et al, 2014; Bock et al, 13 2015). Therefore, these maps are likely to be well aligned across subjects, and averaging will preserve 14 many of the retinotopic features found in the maps of individual subjects.…”
mentioning
confidence: 95%
“…By providing the parameters of the solved 10 models, we substantially lower the barrier to entry for scientists to make use of the dataset. 11 12Size and quality of the HCP 7T Retinotopy Dataset 13 14Although researchers frequently collect, and occasionally make public, retinotopy datasets, such datasets 15 have generally included no more than 20 subjects (e.g., Benson et al, 2012). To the best of our 16 knowledge, the HCP 7T Retinotopy Dataset is the largest publicly available dataset by an order of 17 magnitude.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increased power of computational methods now permits investigators to develop and share algorithms that reliably define important anatomical features. There are algorithms for identifying major white-matter fascicles (77)(78)(79)(80), parcellating the cortical surface (81,82), and establishing cytoarchitectonic divisions in stained sections of cortex (83). In this work, we developed a reliable and automated definition of the VOF.…”
Section: Dorsal Vof Endpoints Project To the Transverse Occipital Sulcusmentioning
confidence: 99%
“…Critically, we show changes in white matter tissue properties within the optic radiation that are specific to fascicles projecting from central, foveal locations, those with retinal damage. To do so, we performed an advanced, anatomically precise characterization of the relationship between the locus of retinal damage in AMD (fovea) and the white matter fascicles within the optic radiation projecting to locations of primary visual cortex that represent different eccentricities-fovea, parafoveal and peripheral regions combining anatomical and advanced computational methods (Benson et al 2012(Benson et al , 2014. This fine grade mapping between the retinotopic location of damage and white matter goes beyond previous reports (Prins et al 2016a, b;Hernowo et al 2014;Malania et al 2017).…”
Section: Introductionmentioning
confidence: 99%